Secrets and disclosures: How young children handle secrets - Αναγνωστάκη, Λήδα; Παπαθανασίου, Αθανασία (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The behavior of young children regarding the disclosure of secret information was investigated. Two hundred and nine children, 4-6 years old, participated in an experiment where a puppet, named Zinc, was the protagonist. Children were asked to whom Zinc would disclose pieces of information, some of which are considered secrets. Children could choose between Zinc’s friend, a non-friend, both friend and non-friend, or nobody. Participants were divided in two experimental groups: in the first group a verbal clue was given to the participants that some information might be secret, whereas in the second group no clue was presented. Results showed that young children, like older individuals, handle secrets and non-secrets differently, choosing either to withhold secrets or to share them only with friends, but not with non-friends, therefore following the “restrictive selfdisclosure” pattern. In contrast, young children do not withhold non-secret information but share it both with friends and non-friends. However, young children’s behavior is influenced by verbal clues; when verbal clues regarding potential “secrecy” of the information are given, young children tend to treat all of the information as secret.